Compact object populations over cosmic time - Santos, Lucas Marcelo de Sá Marques dos (2025)
The past decade has seen an explosion in our knowledge of compact object populations. The advent of gravitational-wave (GW) astronomy has revealed 84 black hole-black hole (BHBH) mergers out to redshift z~1, a number which promises to grow to ~300 with the release of data from the fourth LIGO-Virgo-KAGRA Collaboration observing run. Though far fewer, black hole-neutron star (BHNS) mergers have also yielded important clues about the existence of low-mass black holes (BHs), and NSNS mergers about the important role those events play in chemical evolution. We have simultaneously continued to accrue information about Galactic BHs from X-ray binaries, a new class of dormant BHs and the first ever microlensing detection of an isolated BH. The population of neutron stars (NSs) too has continued to reveal new faces, with recent discoveries of new classes of spider binaries, long-period radio sources, a sub-solar mass NS candidate and pulsar halos. While this large zoo of sources represents the potential to understand multiple channels of compact object formation and evolution, connecting them is a challenge. Massive stellar and binary evolution is still highly uncertain, as is the formation of massive stars and multiple systems. In the case of BHs, when accounting for the long coalescence times of compact object binaries, we now have access to populations formed in conditions ranging from the local Universe to, potentially, Population III stars and primordial BHs, with future detectors expected to extend the GW detection horizon as far as z~100. Any hope of leveraging these multiple samples simultaneously, and constraining how compact object populations form and evolve over cosmic time, will first require us to carefully characterize all sources of uncertainty affecting our ability to model such populations. This thesis aims to assess some of the differences between local and high-redshift (i.e., GW) compact object populations, in particular of BHs, and to offer tools for appropriately connecting them in a cosmological context. We begin by demonstrating that one of the longest standing issues in BH populations, the existence of the lower mass gap in the X-ray binary BH mass distribution, is already strongly disfavored by Galactic and GW populations as a whole, suggesting that multiple formation channels are at play in different environments. We follow this up by reviewing the literature and providing an updated catalog of Galactic BH masses, in preparation for a future updated mass distribution. We highlight the proximity between the ~7 Msun peak in Galactic BH masses and the ~9 Msun peak in GW masses, while the secondary ~35 Msun peak in GW masses is absent in the Galaxy. Connecting these two populations involves variations not only of massive stellar evolution, but also potentially of stellar formation over time, which is often simplified in binary population synthesis (BPS) studies. To lay the groundwork for this connection, we develop and introduce BOSSA (Binary Object environment-Sensitive Sampling Algorithm), a new initial sampling code for BPS that accounts for current models for variable, environment-dependent star formation, and accounts in more detail for modern developments in the theory of star formation. We implement BOSSA for the first time with the BPS code COMPAS to generate compact object merger populations under a set of Invariant and a set of Varying, environment-dependent initial conditions. We find that the BHBH merger population is particularly sensitive to initial conditions, and that the Varying model leads to a ~9 Msol peak in merging BH masses for z<1.6, as is observed, but shifts to a ~16 Msun peak at higher redshifts. We demonstrate that star formation uncertainties have an impact comparable to evolution uncertainties on synthetic populations. Finally, we return to the issue of the ~35 Msun peak, and show how preliminary results from detailed stellar evolution simulations with the MESA code suggest that chemically homogeneously evolving stars might be able to explain it as a consequence of rotational mixing and enhanced wind mass loss.